Climate change perceptions and experiences from tourists visiting popular destinations in South Africa - Lazarus Chapungu; Malebajoa Anicia Maoela; Nthivhiseni Mashula; Hlengiwe Kunene; Godwell Nhamo (Cogent Social Sciences, 2024)
Popular tourism destinations are not insulated from climate change variability and vulnerability. Conversely, these destinations also contribute to climate change. Although several studies have investigated the climate change-tourism nexus, there remains limited knowledge regarding tourist perceptions of climate change on popular African destinations. This study examines tourist perceptions of climate change at the Sun City Resort, a popular destination in South Africa attracting both domestic and international tourists all year round. Data were generated from a survey of 278 tourist participants. The data were analysed in JMP Pro generating descriptive statistics to determine variable and response frequencies, and Structural Equation Modelling (SEM) to examine the relationships, mediations, and associations among key constructs. The results reveal significant associations among climate change awareness, climate change experiences, climate change impacts, and response strategies. Most tourists are familiar with climate change and its existential and potential impacts on the resort. The most prominent weather events include heatwaves, heavy rainfall, and droughts. The impacts include water scarcity, disruption of recreational activities, and destruction of habitats. Low carbon transport systems and green accommodation facilities, carbon friendly activities, investing in climate disaster early warning systems, climate-proofed infrastructure, ensuring facilities and upgrading of disaster rescue operations were highlighted as suitable response strategies. The study concludes that tourists are generally conscious of climate change, and they have knowledge of the necessary actions to ensure popular destination suitability in the face of climate change. The study opens the possibility for crafting destination specific climate action plans that promote destination sustainability.